Clean Water Quality Study in Bima City - Asryadin Asryadin; Adhi Aqwam; Hetti Koes Endang; Rizka Khairunnisa; Jumratul Nurhidayah; Hasan Hasan; Muhammad Rahadian; Fahrul Annas; M. Ichwanul Muslimin; Haerul Annas; Israjunna Israjunna (Postgraduate, University of Mataram, 2023)
Changes in water quality are the main focus in water management because they can have a major impact on the ecosystem. Water quality includes physical, chemical and biological conditions. Coverage of clean water and drinking water inspection data in Bima City reached 97.41%, while the feasibility percentage based on clean water and drinking water quality tests only reached 51.13%. The low percentage of appropriate clean water quality requires special attention. Based on this, researchers studied problems related to water quality, supply and level of need for clean water in Bima City. This research is an analytical observational study, and sampling was carried out using a non-random purposive sampling technique, and analyzed descriptively. Based on the results of physical water quality tests on 31 samples, the results showed that the physical quality of water met the requirements, the chemical quality of water in all measured samples met the requirements for class 1 and 2 clean water quality standards for the parameters DO, COD, total chlorine, nitrate, nitrite, and six valence chrome, while the BOD, Phosphate and Iron values did not meet the requirements (1/31 samples). The biological quality test showed that 12 samples did not meet the requirements for total coliforms (38.7%) and 3 samples showed the presence of E. coli bacteria (9.7%). On the other hand, it was recorded that 95.8% of respondents used shallow drilled wells for clean water; pump wells for 12.5% of respondents; PDAM constituted 16.6% of respondents; shallow drilled wells and PDAM 16.6%; and those using shallow drilled wells and hand pump wells 12.5%. Meanwhile, 37.5% use clean, untreated water and 62.5% use refilled drinking water.